Nacional'no-kul'turna modal'nist' avtors'kich rozdumiv v ukrainskich prozovich tekstach kincâ XX- počatku XXI st. - Golojuch, Larisa (Stylistyka, 2020)
There paper deals with the author’s modality in Ukrainian fiction of the end of the 20th and the beginning of the 21st century. The author seems to be the creator of the individual idiolect and the specific mentality bearer. National cultural author’s modality in the analyzed case can be realized through the activation of the lexemes such as: person, politics, village, time, Ukraine, people etc.